Breeding methods and reproductive parameters of Zebu cattle with genealogical records in Costa Rica - Vásquez Loaiza, Marilyn; Molina Coto, Roger (Agronomía Mesoamericana, 2021)
Introduction. In Costa Rica, the population of cattle with a genealogical record of the Association of Breeders of Zebu Cattle (ASOCEBU), did not have a reproductive characterization or parameters such as age at first calving (EPP) or calving interval (IEP), which limits the analysis, genetic, and productive progress of the breeds. Objective. Characterize the types of methods used to breed pure zebu breeds and calculate the EPP and IEP of a pure gray Brahman population in Costa Rica. Materials and methods. The ASOCEBÚ database from Costa Rica, updated to March, 2018 was used. 10,995 records of the Gray Brahman, Nelore, Red Brahman, Gyr, Guzerat, and Indubrasil breeds were analyzed. The distribution of the animals was calculated according to the types of reproduction used. Of the 32.7 % of the gray Brahman population in ASOCEBÚ from the Huetar Atlántica, Brunca, and Chorotega regions, the EPP and IEP were calculated. Results. The natural mounting was the type of most used method (57.8 %) for the reproduction of zebu animals followed by artificial insemination (26 %) and embryo transfer (16.2 %). The average EPP in the Gray Brahman breed was 41.4 months with an IEP of 548.9 days. Conclusions. It is necessary to select animals with greater sexual precocity and give them the conditions to reduce PPE and IEP. The use of artificial insemination improved the reproductive performance of pure Brahman animals. Breed associations can promote the improvement of animals they register through records and analysis of zootechnical parameters.